DNA fragmentation induced by all‐trans retinoic acid and its steroidal analogue EA‐4 in C2C12 mouse and HL‐60 human leukemic cells in vitro. Issue 8 (2nd August 2013) - Alakhras, Raghda S.; Stephanou, Georgia; Demopoulos, Nikos A.; Grintzalis, Konstantinos; Georgiou, Christos D.; Nikolaropoulos, Sotirios S.
ABSTRACT We have recently shown that retinoic acid induces micronucleation mainly via chromosome breakage (Alakhras et al. Cancer Lett 2011; 306: 15–26). To further study retinoic acid clastogenicity and evaluate DNA damaging potential we investigated the ability of (a) all‐trans retinoic acid and its steroidal analogue EA‐4 to induce DNA fragmentation by using Comet assay under alkaline unwinding and neutral condition electrophoresis, and (b) the retinoids under study to induce small (0–1 kb) DNA fragments. Two cell lines, C2C12 mouse cells and HL‐60 human leukemic cells were used in this study. We found that all‐trans retinoic acid and its steroidal analogue EA‐4 (a) provoke DNA migration due to DNA fragmentation as it is shown by the increased values of Comet parameters, and (b) induce significantly small‐size fragmented genomic DNA as indicated by the quantification of necrotic/apoptotic small DNA segments in both cell systems. A different response between the two cell lines was observed in relation to retinoid ability to increase the percentage of DNA in the tail as well as break DNA in to small fragments. Our findings confirm the ability of retinoic acid to provoke micronucleation by disrupting DNA into fragments, among which small pieces of double‐stranded DNA up to 1 kb are identified. Copyright © 2013 John Wiley & Sons, Ltd.